Translocation of trace elements in the system "Mother-placenta-fetus" in rats with physiological pregnancy and under conditions of lead exposure. - Biletska, E. M.; Onul, N. М. (Medicni Perspektivi, 2014)
Heavy metals are the second major environmental pollutants. Especially toxic is lead, increased content of which in the body of a pregnant determines the development of pregnancy, childbirth and postpartum period complications and is potentiated by deficiency of essential trace elements - zinc and copper. Article presents the results of impact of solutions of lead acetate and citrate in experimental models. Solutions of metals were injected into the stomach through a tube once a day during 19 days of pregnancy in the dose of 0,05 mg/kg in the form of inorganic compound - lead acetate and in organic form – lead citrate. The content of trace elements - lead, cadmium, copper and zinc were determined by stripping voltamperometry. In addition, indices of placental and fetal accumulation, as well as index of transplacental migration were calculated. Effect of lead during pregnancy in all biosubstrates is increased by 1,3-1,9 times as compared with the control group. This causes imbalance of essential trace elements due to significant reduction in zinc content in all the studied biological substrates. Prolonged contact with lead during pregnancy leads to disruption of placenta, inability of the placenta to fully protect the fetus from excessive intranatal influence of xenobiotics.